Relation between immediate postpartum APGAR score with umblical cord blood pH and fetal distress - Pathak, Varuna; Sahu, Deep Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The one-minute Apgar score, proven useful for rapid assessment of the neonate, is often poorly correlated with other indicators of intrauterine well-being. Fetal asphyxia is directly associated with neonatal acidosis. Umbilical cord pH is best indicator of fetal hypoxemia and hypoxemia leads to neonatal acidosis. In today scenario, fetal distress is the leading indication of emergency cesarean section. Methods: A observational cross-sectional study conducted of one year between march 2017 to February 2018; of full-term obstetric patients undergoing emergency cesarean section for fetal distress as an indication. All patients included are term gestation with low risk pregnancy excluding medical disorders and other complications of pregnancy. Immediately after delivery umbilical artertial cord blood from placental site collected and sent for pH determination and Apgar score calculated of newborn. Results: Emergency cesarean section was being done for fetal distress diagnosed based on guidelines for Intermittent auscultation; maximum patients had fetal bradycardia (240) followed by fetal tachycardia (12) and irregular rhythm (18). Relation between pH value and the fetal outcome babies who had low pH value. i.e. <7.1; had maximum referrals with poor Apgar score at 1 min (<3) and at 5 min (<3). Out of 270 babies 18 had Apgar score <3 at 1 min, out of which 10 continued to have Apgar score <3 at 5 mins. These babies were referred to department of pediatrics and were not alive beyond day 2-4. Conclusions: The values of mean Apgar score and cord blood pH decreases, which is inversely proportion to duration and severity of intrauterine/intra partum asphyxia. Umbilical arterial cord blood pH correlation was found to be significant with Apgar score in neonates delivered with indication as fetal distress.